Large‐Ring Cyclodextrins as Chiral Selectors for Enantiomeric Pharmaceuticals. (1st April 2019) - Sonnendecker, Christian; Thürmann, Sebastian; Przybylski, Cédric; Zitzmann, Franziska D.; Heinke, Nicole; Krauke, Yannick; Monks, Kate; Robitzki, Andrea A.; Belder, Detlev; Zimmermann, Wolfgang
Abstract: Large‐ring cyclodextrins (CD) are cyclic glucans composed of 9 or more α‐1, 4‐linked glucose units. They are minor side products of bacterial glucanotransferases (CGTases, EC 2.4.1.19) and have previously been available only in very small amounts for studies of their properties in supramolecular complex formation reactions. We engineered a CGTase to synthesize mainly large‐ring CD facilitating their preparation in larger amounts. By reversed phase chromatography, we obtained single CD samples composed of 10 to 12 glucose units (CD10, CD11, and CD12) with a purity of >90 %. Their identity was confirmed by high resolution mass spectrometry and fragmentation analysis. We demonstrated the non‐toxicity of CD10–CD12 for human cell lines by a cell proliferation assay and impedimetric monitoring. We then showed that CD10 and CD11 are efficient chiral selectors for the capillary electrophoretic separation of the enantiomeric pharmaceuticals fluvastatin, mefloquine, carvedilol, and primaquine. Abstract : Große Zuckerringe : Eine neue Strategie für die biokatalytische Synthese und Aufreinigung ermöglichte die effiziente Herstellung von aus 10–12 Glucoseeinheiten bestehenden Cyclodextrinen, die ungiftig für humane Zelllinien sind. Cyclodextrine aus 10 und 11 Glucoseeinheiten erwiesen sich als effiziente chirale Selektoren für die kapillarelektrophoretische Trennung enantiomerer Pharmazeutika.